CURRENT REALITIES OF STRATEGIC PLANNING OF ENTERPRISES - KULISH, Damir (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the modern realities of strategic planning of enterprises. It has been found that in today's increasingly competitive global corporate market, strategic planning has become a valuable tool for businesses as they strive to balance the diverse interests of key stakeholders—shareholders, employees, customers, and community members.Strategic plans can provide a framework for solving a number of external and internal problems. Developing a robust strategy to address changing market conditions and opportunities, an increasingly global environment, and changing government policies is essential to sustaining resilience. Accordingly, a strategic plan should help create a holistic vision of how to adapt to a changing business environment while addressing challenges related to cash flow, capital availability, and succession planning. These factors help determine the strategic success of an enterprise and influence the ability to ultimately achieve timely value realization. If it is thoughtfully developed and involves all key stakeholders, a strategic plan will bring enormous benefits to owners and managers, contributing to the growth of the enterprise and the creation of value for shareholders in the near term. Ultimately, it will also enable the business and family to manage inevitable ownership transitions or realize shareholder value by providing an optimal range of recapitalization or liquidity strategies.Strategic management is defined as the analysis, evaluation, continuous planning and monitoring of all the needs of an enterprise to achieve its goals and objectives. Effective strategic planning has many advantages. It makes enterprises aware of future opportunities and challenges, anticipate risks and understand what resources will be needed to seize opportunities and overcome strategic challenges.Strategic planning also provides a sense of direction and orients them around a shared mission. It creates standards and accountability. Strategic planning can improve operational plans and efficiency. It also helps organizations limit the time spent on crisis management when they are responding to unexpected changes that they failed to anticipate and prepare for.
Keywords: strategy; planning; strategic planning; management; benefits